Quality of Well Waters of Jaipur District - Paliwal, K V; Gandhi, A P (Annals of Arid Zone, 2016)
Chemical analysis of 92 representative well waters of Chaksu Panchayat Samiti of Jaipur District was carried out to evaluate their quality for irrigation purposes. In general, the waters are highly saline and are of Na-Mg-Ca and Cl-Cos+ RCO3-SO4, type. About 95 per cent samples have more Mg than Ca. Bicarbonate rich waters are low in Ec while Cl and Na are the dominant ions in highly saline waters. It is proposed that ratios of cations and anions should also be expressed while evaluating the quality of irrigation water.